Environmentally friendly green synthesis of reduced graphene oxide using Laurus nobilis, characterization and evaluation of in vitro anticancer activity - Yasemin Budama-Kilinc; Esra Arslan; Bahar Gok; Muge Sari Yilmaz (Materials Research Express)
Graphene, due to its remarkable electrical, mechanical, thermal, and optical characteristics, has become a highly desirable material for scientific investigation. A promising method for large-scale production involves the reduction of graphene oxide (GO) derived from graphite through various chemical processes. Although chemical reduction remains the most effective technique for producing reduced graphene oxide (rGO), its environmental impact raises concerns. The researchers are increasingly exploring reduction methods that utilize natural ingredients as a more sustainable alternative to address this. In this study, rGO was synthesized using a green method using bay leaf ( Laurus nobilis ) extracts. The effects of the plant extract concentration, reflux temperature, and time on the reduction of GO were investigated. The prepared rGO samples were characterized using x-ray diffractometer (XRD), Fourier transform infrared (FTIR), ultraviolet-visible spectroscopy (UV–Vis) spectroscopy, and dynamic light scattering (DLS) techniques. Moreover, the interaction of rGOs with DNA was carried out using the UV–Vis absorption titration method. Studies were conducted to determine the anticancer activity of rGO on two different cell lines and the safe dose on the fibroblast cell line. According to the results, the size of rGO nano-sheets was determined as 203 nm ±2.87, and the PdI value was determined as 0.011 ± 0.02. It has been established that rGO can interact with DNA through a groove or electrostatic binding. According to the cytotoxicity study conducted on the L929 cell line, the 50 μg ml ^−1 rGO dose was safe, and its anticancer activity was more effective in the SHSY-5Y cell line than in C6.